Removal of intraosseous hemangioma in frontal bone under direct vision through a small incision - Kim, Hyeon Seok (Arch Craniofac Surg, 2021)
Complete surgical excision within a margin of normal healthy bone is the treatment of choice for intraosseous hemangioma. A 56-year-old man visited with complaints of a firm, mildly tender, immovable, and palpable mass on the right forehead (size: 1.5× 1.5 cm). Non-contrast brain computed tomography performed preoperatively revealed a 1.5 cm heterogenous osteolytic lesion with suspected internal trabeculation in the right frontal bone. Under general anesthesia, a 2 cm transverse incision was made on the forehead skin rather than bicoronal incision. Full-thickness en bloc resection of the frontal bone including the mass was performed. The frontal bone was removed with care taken not to damage the frontal sinus mucosa. The frontal sinus was sealed with a collagen patch (Tachocomb) and a cranioplasty was performed using bone cement. At 6 months postoperative, a clean wound was confirmed without any complications, and there was no local recurrence. Surgical excision of intraosseous hemangioma in the frontal sinus bone can be performed via direct incision or the bicoronal approach. In this case, the direct incision approach was used to achieve smaller scars and faster recovery than the bicoronal approach.